Augmented Reality-Based Learning Media for Computer and Telecommunication Network Engineering in Vocational Schools - Akhiru Ramadhan, Gian; Marta, Rizkayeni; Rahmy Jasril, Ilmiyati; Darni, Resmi (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2025)
Hardware learning in the Computer and Network Engineering (CNE) Program at vocational high schools is often constrained by limited physical practice tools and media, such as static textbooks and 2D images, which are less effective in visualizing three-dimensional objects. This fails to provide an in-depth understanding of complex hardware components, a foundational skill in vocational education. Augmented Reality (AR) is one of the technologies with great potential to improve learning quality. This study is a Research and Development (R&D) project that aims to design and develop a comprehensive AR-based learning media. The development process was carried out using the Multimedia Development Life Cycle (MDLC) method, consisting of concept, design, material collecting, assembly, testing, and distribution. The novelty of this research lies in its integration of three domains—computer hardware, basic network devices, and fiber optic and telecommunication tools—aligned with the Kurikulum Merdeka learning outcomes. Application feasibility was evaluated in two stages: functional testing using the User Acceptance Testing (UAT) method involving 10 students and validation by media and material experts (two media experts and two material experts). The development resulted in a functional learning media containing 13 interactive 3D models and a quiz feature. Based on the UAT results, all main functionalities—including menu navigation, 3D object visualization, user interaction, and quiz systems—performed as expected. Furthermore, the expert validation yielded an average Aiken's V score of 0.90, categorizing the media as "highly valid". It is concluded that this AR-based learning media is both functionally feasible and highly valid as an innovative instructional tool to enhance students’ understanding of computer and network hardware.Keywords— Augmented Reality, Learning Media, Marker-Based AR, Android, Computer Hardware